PENGARUH PEMBERIAN PROBIOTIK DENGAN WAKTU BERBEDA TERHADAP PERTUMBUHAN DAN KELULUSHIDUPAN IKAN PATIN (Pangasius sp) DAN SAYUR SAWI (Brassica juncea L) DALAM SISTEM AKUAPONIK - Karel K Duka; Felix Rebhung; Yuliana Salosso (Nusa Cendana University, 2019)
This study aims to determine the effect of Probiotic Feeding and the most appropriate time in improving Growth and survivalPatin Fish (Pangasius sp) and VegetablesSawi (Brassica juncea L) in the Aquaponic System. The research was conducted in April - 2017, at the Faculty of Marine and Fisheries Undana. Type of probiotics used is tiger O2. Provision of probiotics 3 days once, once a week, and 2 weeks once with 12 weeks of maintenance. The data measured were the growth of catfish and vegetablessawi, feed conversion, survival, biomass production and water quality. The results showed that effective growth was found in the C treatment with a value of 0.211 g. The lowest feed conversion was found in treatment C with a value of 0.61g. survival of all treatments 100%. The highest production of fish and vegetables biomass was C treatment with a value of 0.637 kg / m3. From the results obtained showed that giving probiotics degan time of 2 weeks can increase growth, feed conversion and survival patin fish during the study. Keywords:Probiotics, patin fish, vegetables sawi, aquaponic system